Rumen bacterial endotoxins and their possible role in the sudden-death syndrome - Tiruvoor G. Nagaraja; E. Bartley; L. Fina; H. Anthony; H. Leipold (Kansas Agricultural Experiment Station Research Reports, 1979)
We have found that rumen bacteria contain endotoxins that are released into rumen fluid. Also rumen fluid from grain-fed cattle contains considerably more free endotoxin than rumen fluid from hay-fed cattle. Injecting cattle with rumen bacterial endotoxins may be involved with such diseases associated with high-grain feeding as the sudden death syndrome.
Keywords: Cattlemen& #x27; s Day; 1979; Report of progress (Kansas State University. Agricultural Experiment Station); 350; Beef; Endotoxins; Sudden death syndrome